Nøkler til ordforrådet: Om lemmafunksjon, struktur og informasjonstyper i en ny kombinatorisk ordbok over islandsk - Jónsson, Jón Hilmar (Nordiske Studier i Leksikografi, 1995)
A new combinatorial dictionary of Icelandic, Oroastaour, includes a relatively few headwords (ca. 11 000), but these in turn give access to a great number of compounds (ca. 100 000, all told). The compounds under each headword are generally grouped according to meaning, which often gives the user access to a broad and varied vocabulary within a specific semantic field. This aspect is strengthened by cross-references between related headwords. The setup of the syntactic information pays special attention to the variety and variations of usage, as shown in the multiple choice of determiners and functional words in the collocations in which the headwords appear.